2018
DOI: 10.1007/s12567-018-0223-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the rotational vehicle dynamics on the ascent flight trajectory of the SpaceLiner concept

Abstract: During the preliminary design of space transportation systems the vehicle dynamics are commonly reduced to a pointmass model for definition of the flight trajectory. While this approach effectively reduces the number of model parameters in the design process, it neglects the rotational dynamics of the vessel completely. Since the rotational degrees of freedom (DOF) have a significant influence on the vehicle's controllability, a sole analysis of the translational dynamics is insufficient to assess the general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…These correlations have been developed in the past from an extensive range of experiments, in order to estimate aerodynamic coefficients of a vehicle from a simple parametrization of its geometry. Since these correlations require very little computational resources but commonly imply high uncertainty, these results are usually considered during the conceptual design phase only [23]. For CALLISTO these results have therefore only be used for cross-validation, particularly in flight conditions where the other datasets are very sparse.…”
Section: Semi-empirical Correlationsmentioning
confidence: 99%
“…These correlations have been developed in the past from an extensive range of experiments, in order to estimate aerodynamic coefficients of a vehicle from a simple parametrization of its geometry. Since these correlations require very little computational resources but commonly imply high uncertainty, these results are usually considered during the conceptual design phase only [23]. For CALLISTO these results have therefore only be used for cross-validation, particularly in flight conditions where the other datasets are very sparse.…”
Section: Semi-empirical Correlationsmentioning
confidence: 99%
“…Aeroelastic instabilities are some of the critical issues affecting the reliability and safety of military and commercial aircraft [1][2][3]. The tri-wing configuration is usually adopted for large swept-back hypersonic flight vehicles [4,5], such as the American X-37B, the Soviet Union's Buran, the British Hotol, and the German Sanger [6][7][8]. The aileron structure of such flight vehicles is thin, which may lead to the flutter behavior.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative application of the suborbital flights is a point to point transportation. Studies on both spaceport and vehicles can be found in [3][4][5] and [6] The researchers from the Warsaw University of Technology were inspired by the Ansary X-Prize competition and begun to work on their own concept of vehicle for manned suborbital tourism flights [7,8]. The MAS (Modular Airplane System) project consists of two airplanes-a mother plane and a rocket plane (see Fig.…”
Section: Introductionmentioning
confidence: 99%